ISOLASI DAN KARAKTERISTIK BAKTERI NITRIFIKASI PADA LIMBAH PENGOLAHAN IKAN PATIN DI DESA KOTO MESJID SEBAGAI RANCANGAN BOOKLET MATERI BAKTERI KELAS X SMA - Mida Wulandari; Irda Sayuti; Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study aims to determine the characteristics of nitrifying bacteria (nitrifying bacteria) in catfish processing waste in Koto Mesjid Village which are used to design booklets in biology learning material for class X high school bacteria which were conducted from September 2022 to January 2023. This type of research uses experimental and descriptive methods. The parameters used included the morphological characteristics of the bacterial colonies, namely macroscopic observations consisting of colony shape, colony color, colony edges and colony elevation and microscopic observations consisting of gram staining and bacterial cell shape. The results of the study found six bacterial isolates that showed different characteristics, namely having clear white, cream, white, and milky white colors, the shape of the colonies found were round and irregular, the edges of the colonies were wavy, flat and jagged, the elevation of the colonies was flat and raised, the surface of the colony is shiny and not shiny, the cell shape is round and rod, gram is negative and positive. Dominant gram negative bacteria were found.Keywords: Characteristics, Isolate, Booklet